Isometric and Closed-Range Composition Operators between Bloch-Type Spaces - Nina Zorboska (International Journal of Mathematics and Mathematical Sciences)
We present an overview of the known results describing the isometric and closed-range composition operators on different types of holomorphic function spaces. We add new results and give a complete characterization of the isometric univalently induced composition operators acting between Bloch-type spaces. We also add few results on the closed-range determination of composition operators on Bloch-type spaces and present the problems that are still open.